Qualitative Assessment of Community Health and Development Needs in the Flood Prone Nyando Sub-County, Kisumu County, Kenya - Omemo, Peter; Patrick Lutta (Yayasan Sinergi Kawula Muda, 2024)
The County government of Kisumu and Non-Governmental Organizations (NGOs) have been reactive to the plight of the residents of Nyando Sub-County during floods, rather than addressing the community health and development needs. There is a knowledge gap regarding institutional knowledge of the issues that may positively contribute to the resilience of the residents of the flood prone Nyando Sub County. The overall objective of this study was to gain insight of the community health and development needs of the residents of flood prone Nyando Sub-County, Kisumu County in order to inform the county government and local NGOs in the area. A total of 84 participants were assigned into 12 Focus Group Discussions (FGDs). The FGDs covered 10 thematic areas with a variety of questions. Informed consent was sought from the participants during recruitment into the study. The FGDs were conducted in the local Dholuo language, and tape recorded. Transcription of the data was done thematically through content analysis and coding. Common threads from the themes were outlined as; desire to improved access to safe domestic water, construction of more health facilities, employment of more nurses and other healthcare workers, improved primary schools’ infrastructure, creation of income generation activities, and improvement of security in the area to avoid cattle rustling. The qualitative assessment indicated that residents understand their needs and lack of safe water, poor health services and infrastructure were the main needs of the residents of Nyando Sub County.